Arginine: Its pKa value revisited. (22nd March 2015) - Fitch, Carolyn A.; Platzer, Gerald; Okon, Mark; Garcia‐Moreno E., Bertrand; McIntosh, Lawrence P.
Abstract: Using complementary approaches of potentiometry and NMR spectroscopy, we have determined that the equilibrium acid dissociation constant (p K a value) of the arginine guanidinium group is 13.8 ± 0.1. This is substantially higher than that of ∼12 often used in structure‐based electrostatics calculations and cited in biochemistry textbooks. The revised intrinsic p K a value helps explains why arginine side chains in proteins are always predominantly charged, even at pH values as great as 10. The high p K a value also reinforces the observation that arginine side chains are invariably protonated under physiological conditions of near neutral pH. This occurs even when the guanidinium moiety is buried in a hydrophobic micro‐environment, such as that inside a protein or a lipid membrane, thought to be incompatible with the presence of a charged group.